Comparison of clinical outcomes between cone beam CT-guided thermal ablation and helical tomotherapy in pulmonary metastases from hepatocellular carcinoma - Wang, Feihang; Fan, Shaonan; Shi, Qin; Zhao, Danyang; Sun, Huiyi; Sothea, Yav; Wu, Mengfei; Song, Huadan; Chen, Yi; Cheng, Jiemin; Zeng, Zhaochong; Yan, Zhiping; et al. (Frontiers in Oncology, 2022)
Objective This retrospective study compares the clinical results of cone beam CT (CBCT)-guided thermal ablation with those of helical tomotherapy in hepatocellular carcinoma (HCC) patients with pulmonary metastases. Methods A total of 110 patients undergoing thermal ablation or helical tomotherapy for pulmonary metastases from April 2014 to December 2020 were included in the study. The endpoints were local tumor progression-free survival (LTPFS), overall survival (OS), and complications. Univariate and multivariate analyses using the Cox proportional hazard model were conducted to identify independent factors (univariate: P < 0.1; multivariate: P < 0.05). The Kaplan–Meier method was used to calculate the LTPFS and OS rates. Results The results of 106 patients were taken into the final analysis. The 1- and 3-year LTPFS rates were 50 and 19% for the thermal ablation group and 65 and 25% for the helical tomotherapy group. The median LTPFS in the thermal ablation group was 12.1 months, while it was 18.8 months in the helical tomotherapy group (P = 0.25). The 1- and 3-year OS rates were 75 and 26% for the thermal ablation group and 77 and 37% for the helical tomotherapy group. The median OS was 18.0 months in the thermal ablation group and 23.4 months in the helical tomotherapy group (P = 0.38). The multivariate analyses found that α-fetoprotein (AFP) at <400 ng/ml (P = 0.003) was significantly associated with better LTPFS. Tumor number <3 and AFP <400 ng/ml were favorable prognostic factors for OS. There were no grades 3–5 adverse events in both groups. Grade 2 was recorded in three patients (4.8%) in the thermal ablation group and two patients (4.7%) in the helical tomotherapy group. Conclusions For pulmonary metastases from HCC, CBCT-guided thermal ablation and helical tomotherapy provided comparable clinical effects and safety.